Measuring the labour income share of developing countries: Learning from social accounting matrices - Katharina Trapp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper is the first to address the challenges of measuring the labour income share of developing countries. The poor availability and reliability of national accounts data, and the fact that self-employed people, whose labour income is hard to capture, account for a major share of the workforce and often work in the informal sector, render its computation difficult. I consult social accounting matrices as an additional source of information to construct a labour share dataset backed up with microeconomic evidence. First descriptive results show a significant downward trend in labour shares of developing countries since the early 1990s.
Keywords: E25; O15; 330; income distribution; labour share